Stress Responses in Plants 2015
DOI: 10.1007/978-3-319-13368-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Response of Wheat Seedlings to Combined Effect of Drought and Salinity

Abstract: In field conditions the plants are most commonly subjected to simultaneous effects of multiple stresses. The mechanisms of plant tolerance to salinity and drought are physiologically connected and overlapping, but some aspects of physiology and metabolism may differ when in the experiment salt and water stress is used separately or both stresses are used simultaneously. Physiological and biochemical reactions of the plants under combined effect of the drought and salinity are unique, which cannot be directly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 193 publications
(256 reference statements)
0
4
0
Order By: Relevance
“…It is clear that P. sargentii increased the SLW under heavy drought to reduce the leaf size, which is advantageous, as it could reduce canopy temperature and improve water use efficiency [41]. The RWC values of MS and SS leaves decreased during the drying cycles as a result of dehydration of the cells, which could have contributed to a relative change in cell volume of leaf tissues [45] and to the maintenance or even decrease in the Ψo values through lower hydration levels [46]. The fact that gs was equal or greater than 100 mmol m −2 s −1 at the most critical moments of the SS strategy (Table 1) supports the evidence that SS leaves did not reach the lower limit of RWC, where tree regulation is deficient, and metabolism is unable to maintain vital functions [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that P. sargentii increased the SLW under heavy drought to reduce the leaf size, which is advantageous, as it could reduce canopy temperature and improve water use efficiency [41]. The RWC values of MS and SS leaves decreased during the drying cycles as a result of dehydration of the cells, which could have contributed to a relative change in cell volume of leaf tissues [45] and to the maintenance or even decrease in the Ψo values through lower hydration levels [46]. The fact that gs was equal or greater than 100 mmol m −2 s −1 at the most critical moments of the SS strategy (Table 1) supports the evidence that SS leaves did not reach the lower limit of RWC, where tree regulation is deficient, and metabolism is unable to maintain vital functions [47].…”
Section: Discussionmentioning
confidence: 99%
“…Free Pro accumulates in plants in response to a wide range of abiotic and biotic stresses. Most of the data on the regulation of Pro-metabolism were obtained on plants grown under conditions of salt and osmotic stress (Ivanov 2015). In our experiments with CO2 deficiency, an increase in the Pro concentration in the leaves was also observed (Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Under unfavorable environmental conditions, the accumulation of proline (Pro) is often observed in plant leaves, the synthesis of which is most often explained by the activation of specific biochemical mechanisms to counteract the harmful effects of stress. We have previously shown that there is a direct correlation between the change in stomatal conductance and the formation of Pro in the leaves of wheat plants (Ivanov 2015). A decrease in CO2 fixation due to stomatal closure under stress conditions also leads to the C/N imbalance and the accumulation of excessive amounts of nitrogen-containing substances, for example, Pro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation